Pheochromocytoma presenting with severe abdominal pain and abnormal liver enzymes. Issue 8 (15th August 2021) - Habib, Mhd Baraa; Abdelrazek, Mohamed; Alatasi, Sali; Mohamed, Mouhand F. H.; Ali, Hamda; Hamad, Mohamad Khair
Abstract: Pheochromocytoma can present with right hypochondrial pain, elevated liver enzymes, and a misleading appearance on ultrasound scan mimicking hepatic mass due to the proximity of adrenal masses to the liver. Abstract : Pheochromocytoma can present with right hypochondrial pain, elevated liver enzymes, and a misleading appearance on ultrasound scan mimicking hepatic mass due to the proximity of adrenal masses to the liver.